Relationship Between Safety Management Practices And Safety Compliance Among Construction Workers In Kedah Rubber City - Nur Afifah, Abdul Hisham (2024)
Being the main contributor to the economic growth, construction sector has been known as a complicated industry that showed worldwide safety disparity and has received least attention on risk management with regard to human resource. Therefore, this study aims to examine how safety management practices (management commitment, safety training, employees’ involvement, safety rules and regulations, safety communication and feedback, safety promotion policies) relates to the safety compliance among construction workers in Kedah Rubber City site. A quantitative research design was employed in this study. Self-administered questionnaires prepared in Bahasa Malaysia and English were used as a tool for data collection. Simple random sampling technique were used for respondents’ selection so that individuals have equal chances of being selected. Workers were given a session with the presence of the researcher to assist them in answering the questionnaires. There are 126 respondents were involved in the study. Data analysis for the study were Pearson Correlation and Multiple Regression analysis to determine the relationship of safety management practices with safety compliances. The result showed that all six safety management practices have significant relationship with safety compliances. However, regression analysis demonstrates that only management commitment, safety communication and feedback, safety rules and procedure, and safety promotion policies have significant influenced on the safety compliance of workers at Kedah Rubber City. This study contributes to the organization to determine the current issue that hinder safety compliances of workers, so that they can plan for effective solution and promote safety practices effectively.